Sistem Analisis Dan Perancangan Sistem Informasi Pengarsipan Persuratan Menggunakan Metode Waterfall Pada Dinas Lingkungan Hidup Berbasis Web - Kusdarnowo Hantoro; Rahmat Purnomo; Sri Rejeki (Journal of Informatic and Information Security, 2020)
This writing discusses the creation of a correspondence filing information system with the aim of making it easier for the secretariat to archive letters in incoming and outgoing mail data at the Environmental Service, and minimizing data loss, and speeding up the process of retrieval of archived data at the time needed so as not to repetition of archiving so that it is faster and more precise. The development of information systems uses the programming language PHP, HTML, CSS, and Java Script and uses the MySQL database. The information system development method uses the waterfall method. The results of this research can be implemented in the form of a web-based archiving information system.